MODEL OF IDENTITY IN AN EDUCATIONAL DISCOURSE OF COMMUNICATIONS (Education in the 21st Century, 2023)
Starting from John Dewey's concept of reform pedagogy, this work addresses the question of how the relevance of communication can be demonstrated in an educational concept for the development of learners' identities. In the 21st century, the importance of communication and the individuality of learners have become increasingly relevant in educational research. However, there is still a lack of a comprehensive concept that explores the extent to which communication influences an individual's identity.To delve into this topic, the paper initially focuses on communicative action (Jürgen Habermas) to introduce the role of society in shaping identity through morality. The societal level is juxtaposed with the level of the self, drawing on the works of George Herbert Mead and Charles Cooley. These scholars illuminate both interpersonal communication and communication within an individual's self and their impact on identity formation. With this knowledge and an understanding of the dialectic relationship between self and society in identity formation, the paper demonstrates the potential for education to influence the process of identity development through communication in the teaching and learning process.The developed "Model of Identity in an educational discourse of communication" illustrates the interplay of these two levels through their subsystems. It describes how education, particularly through its institutional embodiment in schools, can intervene in and positively affect the process of identity development through communication. In summary, this work explores the nexus between communication, education, and identity development, drawing from Dewey's pedagogical ideas and the sociological theories of Mead and Cooley to propose a model that offers insights into how education can impact the development of individual identities through communication.